2018
DOI: 10.1002/jcp.27110
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70: A promising therapeutic target for myocardial ischemia–reperfusion injury

Abstract: Acute myocardial infarction is a major cause of death worldwide. The most important therapy for limiting ischemic injury and infarct size is timely and efficient myocardial reperfusion treatment, which may instead induce cardiomyocyte necrosis due to myocardial ischemia-reperfusion (I/R) injury. Heat shock protein 70 (HSP70), a stress-inducible protein, is overexpressed during myocardial I/R. The induced HSP70 is shown to regulate several intracellular proteins (e.g., transcription factors, enzymes, and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 114 publications
1
28
0
Order By: Relevance
“…Transgenic expression of Hsp70 or its interacting protein CHIP (Carboxyl terminus of Hsp70-interacting protein (CHIP), a ubiquitin ligase) was protective against doxorubicin-induced cardiomyopathy (Naka et al, 2014;Wang et al, 2016). Furthermore, an aggregate of studies suggest that activation of Hsp70 signaling in protective against cardiac ischemia-reperfusion injury (Song et al, 2019). However, a note of caution is relevant given a role for Hsp70 described in promoting cardiac hypertrophy in response to pressure overload, which is typically pathologic and results in decompensation (Kee et al, 2008).…”
Section: Targeting Heat Shock Proteins For Cardioprotection: Let's Comentioning
confidence: 99%
“…Transgenic expression of Hsp70 or its interacting protein CHIP (Carboxyl terminus of Hsp70-interacting protein (CHIP), a ubiquitin ligase) was protective against doxorubicin-induced cardiomyopathy (Naka et al, 2014;Wang et al, 2016). Furthermore, an aggregate of studies suggest that activation of Hsp70 signaling in protective against cardiac ischemia-reperfusion injury (Song et al, 2019). However, a note of caution is relevant given a role for Hsp70 described in promoting cardiac hypertrophy in response to pressure overload, which is typically pathologic and results in decompensation (Kee et al, 2008).…”
Section: Targeting Heat Shock Proteins For Cardioprotection: Let's Comentioning
confidence: 99%
“…Elevating O-GlcNAc levels augments expression of HSPs by heat stress [14,95], while decreasing O-GlcNAc suppresses expression of HSPs [96]. Expression of HSP70 and HSP72 may be protective against IR injury through repression of apoptosis [97,98,99], because they are upregulated by a RIC stimulus [100]. Jones et al showed that HSP70 levels were increased in cardiomyocytes that were protected by PUGNAc against H 2 O 2 injury [20].…”
Section: Mechanisms By Which O-glcnac Confers Protectionmentioning
confidence: 99%
“…Members of the heat shock protein 70 family and have also been linked to cancer and multiple neurodegenerative diseases 37 . Overexpression of HSP70 suppressed ischemia–reperfusion damage, as well as Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease 38 40 . One study found that HSPA8 functions as a safeguard for protein homeostasis and is reduced in brains of Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 243 proteins were shared between all 4 groups (Fig. 3A), whereas ~ 8% (38) and ~ 12% (57) were unique to TBI and TBI RIC groups, respectively. Pathway analysis based on the entire proteome revealed 63 uniquely enriched pathways, 46 (73%) of which were shared across all conditions ( Fig.…”
Section: Tbi Reduced Plasma Concentration Of Amino Acids and Ric Treamentioning
confidence: 99%
See 1 more Smart Citation